What’s traditional about “the traditional funeral”? Funeral rituals and the evolution of the funeral industry in Nova Scotia - Poulter, Gillian (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2011)
The funeral services industry today promotes what it calls “the traditional funeral” as the preferred choice, a description that implies roots in the distant “folk” past. Archival research into the care of the dead in Nova Scotia reveals that the essential elements of the traditional funeral are indeed derived from pre-modern traditions, but have been adapted to modern consumer society by replacing community involvement with professional expertise. The funeral industry evolved slowly in Nova Scotia, particularly in rural areas where it took longer for services such as embalming to become available. Research shows that the transition from family control to professionalized funeral services was uneven, and in many cases did not happen until the 1950s – some decades later than was typical elsewhere. Consideration of the changing discourse of death suggests that the shift from community to traditional funerals had consequences for our experience of death.